Meningkatkan Kemampuan Berpikir Kritis pada PAKBP dengan Model PBL Berbantuan Media Audio-Visual Materi Allah Membimbing Umat Israel Fase B SDN 071096 Mandrehe - Barnabas Berkat Gulo (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve students' critical thinking skills in Catholic Religious Education through the implementation of Project-Based Learning (PBL) models assisted by audio-visual media. The focus of this research is the material